PENGARUH KURIKULUM MERDEKA TERHADAP HASIL BELAJAR MATA PELAJARAN AKIDAH AKHLAK KELAS PROGRAM KHUSUS DI MTS MUHAMMADIYAH BLIMBING SUKOHARJO TAHUN AJARAN 2024/2025 - Ayuningtyas, Feronika Ananda; Rochmawan, Alfian Eko; Ibadu Rahman, Yahya (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to: 1) determine the independent curriculum of special program classes at MTs Muhammadiyah Blimbing in the 2024/2025 Academic Year, 2) determine the learning outcomes of the subject of aqidah akhlak independent special program classes at Mts Muhammadiyah Blimbing in the 2024/2025 Academic Year, 3) determine the effect of the independent curriculum on the learning outcomes of aqidah akhlak special program classes at Mts Muhammadiyah Blimbing in the 2024/2025 Academic Year. This type of research used quantitative with descriptive analysis. The population in this study were 116 students in the special program class. While the sample of this study was 55 students. Data collection techniques used questionnaires and documentation. Data analysis used correlation analysis with data analysis techniques in the form of simple linear regression analysis. For testing the prerequisite test using the normality test and linearity test. The results of the study show that 1) The independent curriculum was classified as moderate with 22 students or 40%, 2) The learning outcomes of faith and morals were classified as lacking with 24 students or 44%, 3) From the results of data analysis, the independent curriculum on learning outcomes had a significant positive effect with a value of 0.001 (<0.05). Because the calculated r value of 0.440 is greater than the r table of 0.266. This, H0 is rejected H1 is accepted, so there is a significant influence between the independent curriculum on the learning outcomes of faith and morals in the special program class at MTs Muhammadiyah Blimbing.